Application of Animal-Assisted Therapy in Children with Autism Spectrum Disorders - Mykhaylov, B.; Vodka, M.; Vashkite, I.; Aliieva, T. (Psychiatry, Neurology and Medical Psychology, 2016)
The diagnosis of autism spectrum disorder (ASD) has steadily increased in recent years. Families of children with autism often pursue different interventions in the hope of ameliorating particular aspects associated with ASD. Animal assisted intervention (AAI), which has been defined as the use of an animal to provide therapeutic benefit based on a positive relationship between the client and the animal, is a therapeutic measure for children with autism spectrum disorder (ASD). Used on the basis of the Centre’s psychosocial rehabilitation of children and adolescents, Feldman Ecopark animal-assisted therapy for children with autism spectrum disorder provides a number of perspectives to the child’s benefit: the psychological aspect; the social aspect and the technical aspect. The article describes new combinations of disability treatment called Equine Assisted Therapy and Canistherapy in Ukraine. The results of this study indicate that combined EAT and Canistherapy may have a wide range of therapeutic benefits for children with ASD; such program is a unique form of therapy as it can influence so many areas of physical and psychological functioning.